Polymeric Membrane for CO2/CH4 Separation - N., Sazali; W. N. W., Salleh; A. F., Ismail (Materials Research Foundations, 2021)
This chapter presents a critical overview of polymeric membrane applications for CO2/CH4 separation. Comparative summary of availability and practice of different gas separation methods are outlined to give a state-of-the-art view of this technology. Detailed discussions on polymer-based membranes are also discussed in this work, highlighting the mechanism of selective gas permeation through the membranes. Future direction is discussed for possible new experimental design to maximize the membrane performances in separation of CO2/CH4.